Influence of hydraulic properties on the slope stability of unsaturated soil from the garinono formation in Sabah - Suleiman Nassor; Siti Jahara Matlan; Nazaruddin Abdul Taha; Muhammad Mukhlisin (Research Institute, Rangsit University, 2024)
This study investigates the hydraulic response and stability of silty clays from the Garinono Formation during the rainy season, utilizing peak monthly rainfall data recorded over a decade by the Department of Irrigation and Drainage, Sabah. The research focuses on the impact of rainfall infiltration on slope stability under extreme hydrological conditions, modelled using a 31-day antecedent rainfall event from January 2011. The study incorporates both field and laboratory data, assessing the Soil-Water Characteristic Curve (SWCC) and bulk density for three distinct soil samples: (i) MI (Intermediate Plasticity Silt), (ii) ML (Low Plasticity Silt), and (iii) CI (Intermediate Plasticity Clay). The SWCC and hydraulic properties were characterized using the Fredlund, & Xing (1994) model, with subsequent numerical simulations conducted using GEO-SLOPE International. Results indicated that sample (ii) ML exhibited increased cumulative water volume with rising rainfall intensity, influenced by its saturated and unsaturated hydraulic conductivity, as well as the FX model's fitting parameter . The study revealed that high ratios in samples (i) MI and (iii) CI led to greater runoff and reduced infiltration, characterized by lower water storage and higher discharge rates. Conversely, lower ratios in sample (ii) ML facilitated infiltration, increasing water storage and reducing discharge rates. A notable decrease in matric suction was observed during rainfall, with sample (ii) ML showing the most significant reductions, leading to early and substantial decreases in the Factor of Safety (FS), indicating potential instability. In contrast, samples (i) MI and (iii) CI maintained higher stability due to negative Pore-Water Pressure (PWP) and minimal suction reductions. These findings underscore the critical influence of soil permeability on slope hydrological response and stability during intense rainfall events. This study contributes to the understanding of the hydro-mechanical behaviour of the Garinono Formation, with implications for geotechnical design and slope stability analysis in tropical regions.